Continuing the Journey of Education, Training and Research - Bhatta, Mina; Bagale, Shiba (Journal of Training and Development, 2025)
The Journal of Training and Development, Volume 7 has been published with the objective of sharing knowledge and recent research findings in the field of Technical and Vocational Education and Training (TVET). This publication has a collection of valuable articles from TVET experts, scholars and educationists. The articles in this journal are valuable resources for the scholars, educationists, TVET experts and stakeholders. This issue consists of seven articles on different aspects of training and development. The article “Enhancing Rural Women's Technical and Vocational Capability through Homestay Initiatives in Nepal: An Ethnographic Exploration” written by Chet Nath Kanel, Dr. Prakash Chandra Bhattarai, Dr. Laxman Gnawali explores the enhancement of rural women’s technical skills and confidence through homestay. Homestay tourism contributes significantly transferring technical knowledge and vocational skills, boosting women’s confidence and motivation to engage in entrepreneurship. However, challenges arise due to low literacy level, limited education and minimal exposure to modern practices. The study emphasizes the need for accessible training programs in local languages or simple Nepali language, supplemented with regarding materials, continuous facilitation and support to enhance the learning and capacity development. The article penned by Nirmala Mailani, “Challenges and Opportunities for Industry-School Partnerships in Implementing Apprenticeships: A Case Study of Lumbini Province, Nepal” is about the assessment of status of apprenticeship programs. The writer highlights the importance of collaboration between Technical and Vocational Education and Training (TVET) institutions and industries, which helps to promote employability of the graduates. She further focuses on the partnership for enhancement of TVET system and addressing the labour market demand. The challenges include limited industry participation, inadequate supportive legislation and need for cultural shifts in how company view their roles for workforce development. The article “Panchakosha: Foundations for Holistic Child Development” written by Er. Purushottam Chapagain highlights on the Panchakosha Theory which provides a holistic framework for understanding human development. This theory bridges Eastern and Western educational philosophies applying diverse teaching methods. The writer emphasizes the significance of nurturing the physical, emotional and intellectual dimensions by incorporating yoga, nidra, meditation, yoga philosophy and mindful nutrition practices. The writer highlights the practical strategies, including yoga practices and storytelling to align the pedagogy with holistic child development principles. Sambedan Koirala focuses on the gap between demand and supply of the workforce in his article “TVET in Nepal: Scope and the Associated Challenges”. The writer highlights the establishment of CTEVT for the institutionalized formal training programs aiming to produce skilled human resources to support economic development. He further summarizes the challenges faced by TVET, mismatch between workforce supply and demand, limited enrollment in technical programs compared to capacity and issues with instructor quality. He concludes that strengthening TVET is crucial for fostering self-reliance, entrepreneurship and reducing unemployment in Nepal. The article “Impact of Technical and Vocational Education and Training in ABCD Approach in Nepal” by Raj Bahadur Giri focuses on social cohesion, economic resilience and economic empowerment for holistic development of TVET. His emphasis on the ABCD approach helps to utilize local assets and capacities for sustainable, community rooted solutions. The study highlights the role of TVET in equipping individuals with employable skills, driving transformative changes, fostering entrepreneurship and expanding livelihood opportunities contributing to inclusive development, economic growth and poverty reduction. Dev Krishna KC and Bikash Ghaju jointly penned the article “Technical Education in Community Schools (TECS) Instructors’ Experience in Their Retention: A Narrative Study”, which explores the reasons behind the instructor’s retention. The findings of the study suggest that the retention is influenced by both personal and professional considerations. He further adds that low pay and lack of job security lead to dissatisfaction among instructors. Providing flexible working environment, minimizing bureaucratic bottlenecks, updating curricula with appropriate tools and equipment and offering professional development opportunities are the writer’s recommendations for improving the retention of instructors. The article "Prospects and Challenges for Executing Work-Based Learning Approach in Nepal" authored by Dr. Anoj Bhattarai, examines the prospects and challenges of implementing a work-based learning (WBL) approach in Technical and Vocational Education and Training (TVET) in Nepal. Dr. Bhattarai advocates for a supportive legal framework that mandates employers to provide WBL opportunities to TVET students within their industries. He also emphasizes the need for an increase in the volume of industries and creating a favorable environment for private sector and foreign investment. Additionally, he highlights the importance of raising awareness among guardians about the value of WBL, encouraging them to support their children's participation, and preparing students for learning in work-based settings. Finally, the editorial team expresses its heartfelt gratitude to the authors, reviewers and TITI management, for their invaluable support and collaboration. We also extend our thanks to the Tribhuvan University Central Library (TUCL) for their professional assistance in checking the articles for plagiarism. We look forward to continued cooperation from them in the future. Additionally, the editorial team welcomes feedback on this publication, as we believe it will help further enhance its quality.